Les innovations des agriculteurs en Afrique - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Le document intitulé Farmer Innovation in Africa: A Source of Inspiration for Agricultural Development (2001) résume les résuÉtats de deux programmes régionaux réalisés en Afrique qui ont soutenu des agricu